Consumers' perception of food product craftsmanship: A review of evidence. (January 2020) - Rivaroli, Sergio; Baldi, Beatrice; Spadoni, Roberta
Highlights: We reviewed 36 papers considering the consumer's perspective. We organised the findings in the context of Alphabet Theory. Attitudes are relevant predictors of craft food products. Price is consistently associated with the perception of quality. Craft food consumption is perceived as a meaningful moment of pleasure resulting from a multifaceted experience. A critical discussion on the possible directions of future research is provided. Abstract: The understanding of what the consumer considers as craftsmanship is a sensitive question in the food sector. Despite food label regulations on this issue having undergone partial harmonisation, revealing what the consumer perceives as a craft food is a feat that has yet to be achieved. Drawing upon a review of literature in the field of consumer research, this investigation addresses this knowledge gap. In the light of the Alphabet Theory framework, the review offers a systematic overview of the motives affecting individuals' perception of food product craftsmanship, as well as of the key factors affecting consumer behaviour towards craft foods. The findings provide useful insight to add to the body of extant literature and to discuss the possible directions of research. Moreover, the results can also have relevant importance to support legislators in designing appropriate regulations on craft foods.